The Characteristics of Northeast China Cold Vortex With Different Active Paths in June and Their Relationship With Precipitation and Pre-SST - Fang, Yi-He; Zhang, Meng-Meng; Zhao, Chun-Yu; Gong, Zhi-Qiang; Zhou, Xiao-Yu; Zhang, Wei-Qi (Frontiers in Environmental Science, 2021)
In this study, a K-means clustering (KMC) method was used to identify the paths of the Northeast China (NEC) Cold Vortex (NCCV). The NCCV was divided into four types according to the identified active paths: (1) Eastward movement type (EM); (2) Southeastward long-distance movement type (SLM); (3) Eastward short-distance movement type (ESM); and (4) Southward short-distance movement type (SSM). The characteristics of the four types of the NCCV, along with their impacts on the precipitation during early summer in NEC, were studied. The results showed that the KMC method can effectively divide the NCCV events into four different types. The maintaining days of these four types of the NCCV were found to have obvious interannual and interdecadal variation features. For example, the maintaining days of the EM and ESM types were mainly characterized by interannual variability, while the SLM and SSM types have the obvious 10-13a interdecadal variation along with interannual variability. In terms of the spatial distributions and impacts on precipitation, the EM type was found to appear in the majority of the areas located in NEC, the SLM type mainly occurred in the northwestern region of NEC and the highest rain center was located in the south-central portion, while the ESM type and SSM type were observed precipitation only appear in a small portion of the northeastern region. In addition, it is also observed the distribution of the sea-surface temperature (SST) anomalies had close relationship with the formation of these four types of the NCCV. The tripole distributions of the SST anomalies in the Atlantic Ocean corresponded to the EM type of the NCCV, the positive anomalies of SST in the eastern equatorial Pacific Ocean and negative anomalies in the western equatorial Pacific corresponded to the SLM type, the positive SSTs in the Northwest Pacific correspond to the ESM type, while negative anomalies SST in the western equatorial Pacific Ocean corresponded to the SSM type of the NCCV.